ANALISIS PENERAPAN SISTEM JAMINAN SOSIAL SEBAGAI PERLINDUNGAN HUKUM TENAGA KERJA ASING DI INDONESIA - Dalimunthe, Nikmah; Pratama, Muhammad Riski Anugerah; Lois, Muhammad (LPPM Universitas Bina Bangsa, 2023)
A social security system for workers, especially foreign workers, is also needed as legal protection for foreign workers. The purpose of this research is to find out how the implementation of the social security system that runs at the same time that the social security system acts as legal protection. Researchers in this case look at the applicable laws and government regulations regarding how the national social security system is applied to foreign workers in Indonesia. According to the laws of the social security system administering agency as well as government regulations and regulations of the Ministry of Manpower that foreigners who work for at least 6 months are required to join the Social Security Administration Agency (BPJS) to receive social security provided by the government if there is a risk in work. Foreign workers receive social security such as old age security, work accident insurance and death insurance. Regarding registration for participation in this national social security, mostly if the foreign worker works from an employer other than the state, the employer is obliged to register them and themselves, as well as different contributions that must be paid to BPJS. With this national social security system as legal protection it aims to create justice in work relations, security at work and replacement if there is a risk at work